Monitoring of Shadow Cash Flows Using Computer Modelling - Baturina, Evgeniya Vladimirovna; Litvinenko, Aleksandr Nikolaevich (Economy of Regions, 2018)
The computer simulation of economic systems is a promising tool in the development of the theory of the country’s economic security. We have examined the Russian banking legislation and synthesized judicial economic expertise. This has allowed to develop an algorithm for the investigation of the marker pattern of shadow cash flows. The authors’ algorithm of marker monitoring of cash flow consists of the following sequences. Firstly, we set the time of the first receipt of money and the first withdrawals. Secondly, we compare cash balance of an organization at the beginning of the period with the first withdrawals. Thirdly, under the given condition, the minimum value of interested money flow in these withdrawals is calculated. This value is characterized by the marker parameters and forms a table containing data on the cash flow, recipients and payers, spheres of their activity. And last, on the basis of this table, we build a graph of relationships between the subjects of the shadow economy. The graphs vertices represent these subjects. The visual representation of the graph is a marker pattern of shadow cash flow. The practical importance of this algorithm is due to its applicability in the investigation of economic crimes both at the stage of intelligence operations, and when obtaining proofs of the brought criminal cases in the form of the conclusions of experts-economists. In addition, marker patterns of shadow cash flows can describe the state of the shadow economy of a region as a whole including its dynamics. This expands its parameterization. The created database of the shadow flows of the economy can be also useful for the scientific community. On the basis of the received results, we have developed management decisions to create and administer the information resource of the Bank of Russia “Shadow economy of a region”. This information resource ensures tracking the marker trace of cash flow in the bank environment by the tools of computer modelling.